Analisis Pengaruh Arus dan Tegangan Pengelasan 3 G Conveyor Terhadap Struktur dan Sifat Baja - Wa’addulloh, Mu’izzaddin; Diansisti , Anisa; Purwanto, Purwanto (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
In the world of the PLTU industry, the need for material, especially the need for the sapot process and conveyor repairs, occurs in the world of PLTU, which is installed on the conveyor construction and when connecting materials, different grades are often used and this often occurs in the field during the process of combining plates with different grades. on the sapote. and for installing the plate on the sappot, use grade A and the plate that is often used is the plate for the machine foundation with grade B on the sappot material using low carbon grade A steel. In this research report, welding is carried out and combined with grade A steel which is usually used for sappots. the conveyor is combined with low carbon grade B steel in the construction of the PLTU sapot. Where welding is carried out 3x why this needs to be done is because to know the characteristics of low carbon grade A steel and low carbon grade B steel, whether the characteristics are the same or not because they are used in When grade A steel material runs out in the industry, the testing process uses 3 tests, namely to determine NDT testing (Non Destructive, test), tensile testing, and micro testing for the testing process. (DonyPerdana and Ahmad Bazy Syarif, 2017).